Community-based education: The #lesswaste habit formation by the YukNgaji Club as an Environmental Conservation Effort - A. Alanazi, Meshal Saleh; Muzakki, Muhammad Asgar; Muslimin, JM; Hidayat, Syahrul Ramadhan; Yusof, Nabila; Nukhba, Ghulam Musthafa (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2025)
AbstractThis study explores the YukNgaji community’s #LessWaste campaign as a community-driven Islamic ecotheology model. Amid environmental crises requiring sustainable action, the initiative bridges Islamic stewardship (khalifah) and responsibility (amanah) with ecological awareness. Using qualitative methods—virtual ethnography, community-based education theory, and Living Qur’an-Hadith analysis—data were gathered via observations, interviews, and digital content assessment. Results indicate #LessWaste effectively integrates Islamic ecological values through digital activism and offline practices (e.g., waste donation, reusable items). The campaign functions as both an environmental movement and adaptive educational platform, engaging Muslim youth with modern challenges. It highlights hybrid activism’s role in Islamic education, suggesting applicability across diverse Muslim communities. Future studies should test similar frameworks in varied socio-cultural contexts to evaluate sustained behavioral change.AbstrakPenelitian ini mengkaji kampanye #LessWaste komunitas YukNgaji sebagai model ekoteologi Islam berbasis komunitas. Menghadapi krisis lingkungan yang mendesak kebutuhan aksi berkelanjutan, inisiatif ini menghubungkan prinsip stewardship (khalifah) dan tanggung jawab (amanah) dalam Islam dengan kesadaran ekologis. Dengan metode kualitatif—meliputi etnografi virtual, teori pendidikan berbasis komunitas, dan analisis Living Qur’an-Hadith—data dikumpulkan melalui observasi partisipan, wawancara dengan anggota kunci, dan analisis konten digital. Hasil menunjukkan #LessWaste berhasil mengintegrasikan nilai ekologis Islam melalui aktivisme digital dan praktik offline seperti donasi sampah serta penggunaan barang reusable. Kampanye ini berfungsi ganda sebagai gerakan lingkungan dan platform pendidikan adaptif yang melibatkan generasi muda Muslim dengan isu kontemporer. Temuan menggarisbawahi peran aktivisme hibrid dalam pendidikan Islam serta potensi replikasinya di komunitas Muslim beragam. Studi lanjutan disarankan untuk menguji model serupa dalam konteks sosiokultural berbeda guna menilai dampak jangka panjang pada perubahan perilaku berkelanjutan. How to Cite: Alanazi, M. S. A., Muzakki, M. A., Muslimin, J. M., Hidayat, S. R., Yusof, N. B., & Nukhba, G. M. (2025). Community-based education: The #lesswaste habit formation by the YukNgaji Club as an Environmental Conservation Effort. TARBIYA: Journal of Education in Muslim Society, 11(1), 17-38. doi:10.15408/tjems.v12i1.45474.